Implementation of the Ultra Petita Decision of the Constitutional Court in Indonesian Legal Practice (Study of Constitutional Court Decision Number 30/PUU-XVI/2018) - Rizaldi Abdillah; Diki Okta Dwi Putra; Sandra Firdausi Aprilia; Abdul Rozak (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Court Constitution is a judicial institution new constitution _ formed post amendment to three 1945 Constitution. As a Judicial Institution naturally Court Constitution have authority in interpret constitution. The problem is interpretations Court Constitution to Tested laws _ often cause norm new, thing this considered as ultra petita conducted by the Court Constitution. As a judicial institution that has independent nature already naturally Court Constitution to do interpretations Constitution. Besides that nature text in Constitution which is open (open text) requires there is an interpretation of text that. However implementation to decisions Court Constitution no seldom experience waiver by related institutions.